An Approach to Transfer Biological Solutions Based on the Interaction of Mechanisms to Technical Products. (May 2022) - Bartz, M.; Uttich, E.; Wanieck, K.; Bender, B.; Wartzack, S.
Abstract: Biological solutions are often used for developing technically innovative products in a biomimetic process. However, biological solutions do not always make it into a successful technical product, e.g. due to a lack of knowledge on the mechanisms of action. A new approach is presented for transferring biological solutions based on complex mechanisms of action. It is based on mathematical optimization methods and applied to the lightweight design of the musculoskeletal system. Finally, first technical implementations in the field of robotics, among others, will be presented.